2010
DOI: 10.1007/s11325-010-0337-4
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sleepiness and its determining factors in Chinese obstructive sleep apnea patients

Abstract: EDS is correlated with the severity of OSAHS. More severe patients are characterized by higher ESS score, higher BMI, and progressive worsening of nocturnal hypoxemia. Nocturnal hypoxemia is a major determinant of EDS in Chinese OSAHS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
54
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 28 publications
8
54
2
4
Order By: Relevance
“…The stepwise multiple regression analysis performed to evaluate the correlations of individual clinical and polysomnographic variables with the ESS score revealed that the ESS score significantly correlated with the oxygen desaturation index (ODI), apnoea -hypopnea index (AHI), and body mass index (BMI), and ODI was the strongest determinant of ESS score. 32 In similar study, when a stepwise multiple regression analysis was performed, neck circumference in men and BMI in women were shown to be the strongest predictors of sleep apnoea which is also seen in our study. 33 In a two-phase cross-sectional study, the prevalence and related clinical features of obstructive sleep apnoeahypopnea (OSAH) in the general population were estimated.…”
supporting
confidence: 87%
“…The stepwise multiple regression analysis performed to evaluate the correlations of individual clinical and polysomnographic variables with the ESS score revealed that the ESS score significantly correlated with the oxygen desaturation index (ODI), apnoea -hypopnea index (AHI), and body mass index (BMI), and ODI was the strongest determinant of ESS score. 32 In similar study, when a stepwise multiple regression analysis was performed, neck circumference in men and BMI in women were shown to be the strongest predictors of sleep apnoea which is also seen in our study. 33 In a two-phase cross-sectional study, the prevalence and related clinical features of obstructive sleep apnoeahypopnea (OSAH) in the general population were estimated.…”
supporting
confidence: 87%
“…53 This is in line with the reported discordance between subjective and objective sleepiness measures, 54,55 and our findings. In fact, more recent studies of OSA populations have suggested that desaturating events appear to correlate with subjective, 56 but not objective, sleepiness. 55 The correlation between sleep fragmentation measures and daytime sleepiness frequently accounts for only a small part of the total variance, 47 which is why we initially sought to explore nondesaturating breathing disturbances, regardless of association, as a means of determining whether the sleep-breathing events, in and of themselves, justify their inclusion into the AHI.…”
mentioning
confidence: 99%
“…In ag re ement with the li te ra tu re, we de tec ted that AHI and res pi ra tory-re la ted aro u sals we re mo re im por tant in exp la i ning pre sen ce of EDS. 9,10,16,17 Si mi lar to ot her stu di es, we sho wed that the OSA pa ti ents with EDS we re yo un ger and the re was a ne ga ti ve re la ti ons hip bet we en ESS sco re and age. 16,18 One study in di ca ted a dec re a se in nigh ttime sle ep ef fi ci ency and day ti me sle ep den sity in older com pa red to yo un ger pa ti ents as a re sult of the shift of the he mos ta tic sle ep mec ha nism to wards wa ke ful ness.…”
Section: Discussionmentioning
confidence: 79%